2012
DOI: 10.1007/s10753-012-9448-3
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Effect of Piperine in Adjuvant-Induced Arthritic Rats—a Biochemical Approach

Abstract: The present study was undertaken to investigate the anti-inflammatory effect of piperine against adjuvant-induced arthritis in rats, an experimental model for rheumatoid arthritis and compared it with that of the non-steroidal anti-inflammatory drug indomethacin. Administration of heat-killed Mycobacterium tuberculosis (0. 1 ml) intradermally into the right hind paw of rats resulted in increased paw volume, lysosomal enzymes, glycoproteins and tissue marker enzymes and decreased body weight. However, these cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 27 publications
1
20
0
1
Order By: Relevance
“…However, the boosting of antioxidant defence (enzymatic and non‐enzymatic) system by trikatu supplementation in arthritic rats might be primarily due to the free radical scavenging action of piperine, gingerol and shogaols. These findings are in line with the previous studies conducted in our laboratory . Moreover, the reports on the extracts of Zinger officinale and Piper nigrum on their antioxidant activity supports our claim …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, the boosting of antioxidant defence (enzymatic and non‐enzymatic) system by trikatu supplementation in arthritic rats might be primarily due to the free radical scavenging action of piperine, gingerol and shogaols. These findings are in line with the previous studies conducted in our laboratory . Moreover, the reports on the extracts of Zinger officinale and Piper nigrum on their antioxidant activity supports our claim …”
Section: Discussionsupporting
confidence: 94%
“…Trikatu is believed to promote health, immunity and longevity by strengthening all tissues of the body . In addition, our laboratory has also reported the anti‐arthritic property of trikatu and its active principles such as 6‐shogaol, 6‐gingerol and piperine on different experimental arthritic models . On the foreground of this, an attempt has been made to evaluate its anti‐arthritic effect with respect to various biochemical, immunological, histopathological and radiological parameters in aduvant‐induced arthritic rats.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to this study, Murunikkara et al . reported that the levels of inflammatory infiltration, lysosomal enzymes, lipid peroxidation and TNF‐α were reduced by a 30 mg/kg dose . In a rat arthritis model, piperine was administrated at 20 and 100 mg/kg doses, the results showed that 100 mg/kg piperine group exhibited a significant reduction in inflammatory cell number and paw volume .…”
Section: Discussionmentioning
confidence: 95%
“…Thus, these two methods could be useful for the evaluation of drug-induced PD models. PIP and PLG both have been shown to confer resistance to oxidative stress (Chonpathompikunlert et al, 2011;Raj et al, 2011;Umar et al, 2013) and have anti-inflammatory (Murunikkara et al, 2012;Lee et al, 2013) and anti-cancer effects (Jarvius et al, 2013;Ouyang et al, 2013). Although the mechanistic bases of these effects are not fully understood, mitochondria could be a potential target.…”
Section: Discussionmentioning
confidence: 99%